2002
DOI: 10.1002/jmri.10230
|View full text |Cite
|
Sign up to set email alerts
|

Three‐pool model of white matter

Abstract: Purpose: To investigate the use of a three-pool relaxation model to measure myelin, myelinated-axon, and mixed water-pool fractions in white matter (WM) during myelination. Materials and Methods:MRI at 1.9 Tesla, and conventional spin-echo imaging were used to acquire T1 and T2 relaxation data in 15 normal children ranging in age from 3 months to 13 years 4 months. Three equations with three unknowns were solved to calculate three water-pool fractions for each child in a frontal association-fiber area and a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(190 citation statements)
references
References 28 publications
(53 reference statements)
9
178
3
Order By: Relevance
“…One study of young children who were born prematurely (mean age = 7) revealed longer T2 relaxation times in cerebral white matter compared to age-matched children who were born full-term (Abernethy et al, 2003). Another T2 Relaxometry study, which examined a small group of healthy children ages 3 months to 13 years, found that three-pool modeling revealed changes in myelin that corresponded very well to known patterns of myelination during development (Lancaster et al, 2003). Thus, both T2 Relaxometry and T2R may be useful methods for the study of myelin growth during important developmental periods such as adolescence and may also be applicable to the study of myelin changes during aging.…”
Section: T2 Relaxography (T2r)mentioning
confidence: 95%
“…One study of young children who were born prematurely (mean age = 7) revealed longer T2 relaxation times in cerebral white matter compared to age-matched children who were born full-term (Abernethy et al, 2003). Another T2 Relaxometry study, which examined a small group of healthy children ages 3 months to 13 years, found that three-pool modeling revealed changes in myelin that corresponded very well to known patterns of myelination during development (Lancaster et al, 2003). Thus, both T2 Relaxometry and T2R may be useful methods for the study of myelin growth during important developmental periods such as adolescence and may also be applicable to the study of myelin changes during aging.…”
Section: T2 Relaxography (T2r)mentioning
confidence: 95%
“…A simple technique that would access the degree of myelination of white matter would be very useful in mature animal models of white matter injury such as multiple sclerosis and in immature animal models of white matter injury such as periventricular leukomalacia as well as in human studies. There are various methods available: one approach consists of quantification of myelin bond and free water fractions by a multiexponential analysis of the T 2 decay (Beaulieu et al, 1998;MacKay et al, 1994;Whittall and MacKay, 1989;Lancaster et al, 2003). This is generally performed using a CarrPurcell-Meiboom-Gill (CPMG) or a Turbo Spin-Echo sequences with multiple echo times (Beaulieu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A technique that provides specific and sensitive information about the myelin content was developed based on an analysis of T 2 relaxation times (5,6). It has been reported that the T 2 spectrum of WM and several myelinated tissue samples consists of multiple components (7)(8)(9)(10)(11)(12)(13) and that the short component with T 2 between 10 ms and 50 ms corresponds to the water pool within the myelin sheath (2)(3)(4)(5)(6). Myelin content can therefore be quantitated using the fraction of this short T 2 component.…”
mentioning
confidence: 99%